The roles of strigolactones: Mineral compounds, indole-3 acetic acid and GA3 content in grapevine on drought stress - Çeti̇n, Emine Sema; Canbay, Hale Seçi̇lmi̇ş; Daler, Selda (Journal of Plant Stress Physiology, 2022)
Plants have an extremely important place in the life of living creatures and in the ecological cycle. First of all, they undertake a complex phenomenon such as photosynthesis and perform critical tasks such as being raw material for different industrial branches especially for human and animal nutrition, preventing erosion, contributing to the soil in terms of organic matter, and assuring temperature control. It is also known that the environmental conditions of plants, which have such a significant place in our lives are changing day by day and the plants are faced with a vast number of adverse factors. Plants are affected by these factors of biotic or abiotic origin, which are not suitable for them, and as a consequence, they get stressed. Drought is the leading one of these stress factors. It is clearly acknowledged that endogenous hormones play a major role in the expression of plants as sensitive or tolerant as a result of responses to different types of stresses. It is known that some other substances such as jasmonates, brassinosteroids, salicylic acid and nitric oxide have been included in the endogenous hormones, which were examined under five basic groups until recently, namely auxin, gibberellin, cytokinin, abscisic acid and ethylene. One of these hormones derived from carotenoids is strigolactones (SL). Recent studies demonstrate that this substance produced in plant roots is also at the forefront in terms of stress tolerance. In this study, the effect of SL applications on drought resistance was investigated in Kober 5 BB and 110 R American grapevine rootstocks with different drought tolerance. Rootstocks were treated with 5 and 10 µM SL and exposed to drought stress. In order to measure the effects of SLs on stress, some physical (shoot length, shoot weight, average number of leaves per shoot) and biochemical (mineral substance and endogenous hormones) analysis were carried out. In the study, it was determined that SLs are a sort of hormone that has positive effects in terms of plant growth and development, promotes plant mineral nutrition, and that there is a positive relationship between the synthesis of the endogenous hormones IAA and GA3. According to the results obtained, it is comprehended that SLs can be used as growth regulators to alleviate drought stress.